1960
DOI: 10.1177/004051756003000104
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Wet and Dry Crease Recovery to Wash -Wear Behavior

Abstract: The chemical changes in cellulose fiber which lead to various wet: dry crease re- , covery ratios are reviewed. Covalent cross-linking of a dry fiber enhances both wet and dry recovery, and the ratio of the two values is believed to depend on the relative accessibilities of the fiber to water and to the cross-linking reagent. Water-sensitive links between cellulose chains can give high dry and low wet crease recovery. Cross- linking reactions carried out when the fiber is wet and swollen lead to a higher degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1961
1961
1971
1971

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The use of concentrated solutions of such salts as zinc chloride, thiocyanates, and inorganic bases causes relaxation in the secondary valence forces of the cellulose chains and causes a rise in the wet crease recovery angle of cotton fabric. Steele [70] reported similar results for rayon fabrics. The effect of n~ethvlatiun on wet crease recovery mentioned by Steele [71 ], who dryness and showed that there are sensitive regions between the completely dry and wet states; maxima and minima in the wet recovery angle occurred at water contents of 20-30% for cotton and 30-50% for rayon.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The use of concentrated solutions of such salts as zinc chloride, thiocyanates, and inorganic bases causes relaxation in the secondary valence forces of the cellulose chains and causes a rise in the wet crease recovery angle of cotton fabric. Steele [70] reported similar results for rayon fabrics. The effect of n~ethvlatiun on wet crease recovery mentioned by Steele [71 ], who dryness and showed that there are sensitive regions between the completely dry and wet states; maxima and minima in the wet recovery angle occurred at water contents of 20-30% for cotton and 30-50% for rayon.…”
mentioning
confidence: 56%
“…Steele [70] believed that wet recovery was due to intrachain linking on the C., and C~ hydroxyls in the same anhydroglucose unit (AGU) possibly because in the swollen state the anhydroglucose chains are farther apart and the Cz and C~ hydroxyls more accessible. This, it will be recalled, was the position taken by Wood 1761 on the basis of the reaction of formaldehyde and cellulose catalyzed by i270 sulfuric acid.…”
mentioning
confidence: 99%
“…These are in principle independent of each other, but they probably play simultaneous roles in many known reactions and finishing processes. They are: (1) surface deposition of polymer, which has been described by Steele as a "macroscopic crosslinking" of fibers within yarns, and (2) formation of covalent crosslinks while the fiber is in a swollen state.…”
Section: Discussionmentioning
confidence: 99%
“…These tensile elastic recovery values correlated well with crease recovery. Steele [41 ] presented data indicating that the wash-wear rating of cotton and rayon is a function of wet and dry crease recoveries. It is thus probable that all three tests (crease recovery, wash-wear rating, and elastic recovery) are related to the same fundamental property of cellulose.…”
Section: Resiliencementioning
confidence: 99%